CORRELATION BETWEEN SEVERITY OF PORTAL HYPERTENSIVE GASTROPATHY AND SIZE OF OESOPHAGEAL VARICES IN CIRRHOTIC HEPATITIS-C PATIENTS - Saleem, Khurram; Baig, Faisal Amin; Nida, Mahwish; Javed, Munaza (Journal of Ayub Medical College Abbottabad, 2017)
Background: Portal hypertension can lead to oesophageal varices (EV) and portal hypertensive gastropathy (PHG). The aim of this study is to determine the relationship between severity of Portal hypertensive gastropathy and size of oesophageal varices. Methods: One hundred and ninety-five patients of hepatitis C positive chronic liver disease having oesophageal varices were assessed for severity of portal hypertensive gastropathy. Results: Mild Portal Hypertensive Gastropathy was observed in 16 (8.2 %), moderate in 54 (27.7 %) and severe in 120 (61.6 %) patients. Grade 1 Oesophageal Varices were present in 79 (40.5%) patients, grade 2 in 44(21.9%) patients, grade 3 in 62 (31.8%) and grade 4 in 10 (5.2%) patients. No significant correlation was observed between grades of gastropathy and size of varices. Conclusion: The frequency of portal hypertensive gastropathy was 97.5% in Hepatitis C positive cirrhotic patients having oesophageal varices. Severity of gastropathy is not related to the grade or size of oesophageal varices. Keywords: portal hypertensive gastropathy; oesophageal varices; cirrhosis